Science Amotivation Scale: Validity and Reliability Study - Busra Karaca; Solmaz Aydin (Journal of Education in Science, Environment and Health)
The aim of the present study was to develop the Science Amotivation Scale (SAS) in order to determine amotivation levels among demotivated students in science classes as well as examine the reasons causing amotivation. The participants were 533 students (6th, 7th, and 8th grade) studying across secondary schools located in Kars city centre in Turkey. The development of the scale included; 1) a review of related literature to develop an item pool, 2) interviews with students in a secondary school who were highly demotivated in science classes, 3) consultation with subject matter experts for the draft scale, and 4) exploratory and confirmatory factor analyses. The results suggested that the final scaled included 22 items on a 5-point Likert scale. In addition, the scale had three sub-dimensions: Psychological-Personal Reasons, Family-Environment Related Reasons, and Fear-Anxiety Related Reasons. Exploratory Factor Analysis results showed that factor loadings of items within the scale ranged between .602 and .764. In addition, Confirmatory Factor Analysis results supported the structure of the scale. The reliability coefficient of the scale was calculated as .91. The results also indicated that validity and reliability levels of the scale were high and that the scale, in its current form, can be used to identify the reasons behind students’ amotivation in secondary school science classes.